Ethiopia and Somalia’s Political-Security Entanglement - Majid, Nisar; Abdirahman, Khalif; Ali, Juweria; Adan, Guhad (My University, 2025)
Ethiopia and Somalia have been deeply entangled in political and security terms since the early 1990s as the emergence and rise of the Ethiopian People’s Revolutionary Democratic Front (EPRDF) evolved alongside the collapse and fragmentation of political order in Somalia. This entanglement was initially determined by Ethiopia’s framing of its own Somali Regional State (SRS) and Somalia itself (including Somaliland and Puntland) primarily in security terms. It was also informed by the party-state discipline and strategic coherence of the EPRDF. This research report explores the penetration of a market logic, framed as a political marketplace, that has evolved in this regional entanglement. While this logic informs Somalia’s own political evolution for a much longer period, the years 2010–2018 mark the first critical juncture of this trajectory in Ethiopia. A second critical juncture is associated with the change of regime in Ethiopia in 2018 at both federal and SRS levels. This change continued a market logic but involved a different set of actors and a shift from a monopolistic regime in the SRS to a decentralised and less predictable configuration of actors.
Keywords: Ethiopia; Somalia